Political communication in the noosphere dimension - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article on the basis of socio-philosophical analysis the conceptualization of political communication in the context of noosphere iscarried out.